LEGAL SYSTEM AND LAND OWNERSHIP RELATIONS IN THE SOMAN PERIOD (TAMADDUN NURI JURNALI, 2024)
This article shows the legal system and land ownership relations during the Somonites period, the processes related to the social life of the country.